Pengaruh Model Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Fisika Siswa Kelas X SMK Negeri 1 Batang Angkola - Rangkuti, Yeni Sara; Sri Utami Khoilla Mora Siregar; Eni Sumanti Nasution (Universitas Gara Nusantara Padangsidimpuan, 2023)
This study aims to determine the effect of problem based learning models on students' physics problem solving abilities. This study used a quasi-experimental method with a pretest-posttest control group design. This research was conducted at SMK Negeri 1 Batang Angkola with a total sample of 35 students. Sampling used a simple random sampling technique with data collection using a test of students' Physics Problem Solving Ability with an essay form of 10 questions. Students' physics problem-solving abilities use Polya's theory which includes understanding problems, making plans, doing calculations, and reviewing. Data analysis of the two groups used the t test. based on data processing shows that the value of Sig (2-tailed) <.000 <0.05, ie H0 is rejected. The ability to solve physics problems of students who are taught using the problem-based learning model is higher with an average value of 87.78571 than the problem-solving abilities of students who are taught physics using a learning model that is usually carried out by teachers with conventional learning, namely the 2013 curriculum scientific approach with an average value of 63.14286 . this shows that there is an influence of the problem posing learning model on students' physics problem-solving abilities in the matter of measuring quantities and units